2015
DOI: 10.1007/s10719-015-9643-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in composition and sulfation patterns of glycoaminoglycans in renal cell carcinoma

Abstract: Glycosaminoglycans (GAGs) are heterogeneous, linear, highly charged, anionic polysaccharides consisting of repeating disaccharides units. GAGs have some biological significance in cancer progression (invasion and metastasis) and cell signaling. In different cancer types, GAGs undergo specific structural changes. In the present study, in depth investigation of changes in sulfation pattern and composition of GAGs, heparan sulfate (HS)/heparin (HP), chondroitin sulfate (CS)/dermatan sulfate and hyaluronan (HA) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…For example, VEGF levels may be derived from damaged platelets, while amyloid A is a renowned marker of trauma and various inflammations. Conversely, we and other groups previously provided evidence that the increase of GAG levels in ccRCC patients is likely a product of the tumor itself (30), possibly due to the upregulation of the GAG biosynthetic pathway (14). In addition, the here-reported HRs for the urine score were not only predictors of poor survival in a continuous an independent fashion, but also of much higher magnitude compared to the above mentioned biomarkers (multivariate HR = 5.38 for PFS and 16.43 for OS).…”
Section: Resultsmentioning
confidence: 63%
“…For example, VEGF levels may be derived from damaged platelets, while amyloid A is a renowned marker of trauma and various inflammations. Conversely, we and other groups previously provided evidence that the increase of GAG levels in ccRCC patients is likely a product of the tumor itself (30), possibly due to the upregulation of the GAG biosynthetic pathway (14). In addition, the here-reported HRs for the urine score were not only predictors of poor survival in a continuous an independent fashion, but also of much higher magnitude compared to the above mentioned biomarkers (multivariate HR = 5.38 for PFS and 16.43 for OS).…”
Section: Resultsmentioning
confidence: 63%
“…These disturbances are manifested as a changed sulfation pattern of CS/DS that has common features regardless of the tumor type. First and foremost, a substantial increase in the content of the 6‐ O ‐sulfated and/or unsulfated disaccharides that is observed in a huge majority of cancers is concomitant with a reduction in the 4‐ O ‐sulfation level (Table ). The observed loss of 4‐ O ‐sulfated GalNAc may be one reason for the disappearance of the IdoA residues despite the tumor‐associated upregulation of glucuronic epimerase, which has been found to be characteristic in human cancers such as squamous carcinoma or glioblastoma .…”
Section: The Metabolism Of Cs/ds Is Strongly Altered In the Tumor Stromamentioning
confidence: 99%
“…Unfortunately, only a few studies have focused on this aspect of CS/DS metabolism in the tumor niche . These investigations have reported that the contribution of various disulfated disaccharides to the composition of CS/DS is cancer type‐ and cancer grade‐dependent (Table ). The accumulation of disulfated disaccharides in the CS/DS that exist in the tumor microenvironment can substantially modulate the progression and metastasis of a tumor due to the increased binding potential of these disaccharides .…”
Section: The Metabolism Of Cs/ds Is Strongly Altered In the Tumor Stromamentioning
confidence: 99%
See 1 more Smart Citation
“…This is motivated by the implication of ECM GAG and their PG in a wide variety of biological processes, including embryonic development [11,12], infection [13], inflammation [6,14], wound healing [8] and cancer [14][15][16]. Variation in ECM GAG content and composition is also tissue-specific, age-dependent [17,18] and known to be associated with certain pathologies [19,20]. (2) Chondroitin Sulfate and Dermatan Sulfate also share the same amino sugar unit (GalNac) but their uronic unit is β-d-GlcA and α-l-IdoA, respectively.…”
Section: Introductionmentioning
confidence: 99%